The “house of school” in the in the first decades of Roma Capitale - Cantatore, Lorenzo (Historia y Memoria de la Educación, 2020)
Our research focuses on school buildings constructed in the first decade of Roma Capitale, between the end of the nineteenth and the beginning of twentieth century. The buildings belonged to two categories: 1) edifices readapted as schools (former convents and private dwellings); 2) newly built constructions. School buildings are studied considering their architectural layout, their location within the urban plan, their décor and their symbolic meaning in relation to topography and toponymy. The study method uses interpretation of spaces and places as educational objects that exert an extraordinary influence on the collective imagination. The sources used are: 1) archive documents (Archivio Capitolino) relating to projects and technical relations of architects and engineers; 2) legal documents: laws, measurements, bulletins, ministerial reports on school buildings; 3) publications that document the shaping of public opinion on the importance of endowing the capital with a number of representative and efficient educational sites. The work highlights three main historical trends: 1) the emergenc of laws supporting compulsory education (Casati law, Coppino law) and the social architectural initiatives undertaken in Rome’s poorest and most deprived neighborhoods (Trastevere, Suburra) or in newly built ones for the ascending middle class (Castro Pretorio); 2) the contradiction between rhetoric regarding public educational sites and the scarcity of financial backing for the management of municipal public education and the subsequent, perennial lack of new schooling sites; 3) competition with contemporary religious school architecture, which in comparison with that of public and secular schools was always at the vanguard.